The Effect of Information Technology Use, Organizational Citizenship Behavior, and Task Complexity on Performanceemployees : (Empirical Study on 4 Star Hotels in Badung Regency) - Ni Putu Cahyani Wipagandhi; Ni Luh Sari Widhiyani (International Journal of Management Research and Economics, 2025)
Employee performance is the achievement or target of a person that is carried out to realize the vision, mission, and goals in a company. The importance of collaboration between employee performance and the use of information technology to achieve the targets and goals of the company. This study was conducted to obtain empirical evidence regarding the effect of the use of information technology, organizational citizenship behavior, and task complexity on employee performance. The population in this study were employees of the accounting department at a 4-star hotel in Badung Regency. The sample in this study was taken using a purposive sampling technique to obtain 50 respondents. The data analysis technique used descriptive statistical analysis, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), and multiple linear regression analysis. The results of the analysis provide evidence that the use of information technology and organizational citizenship behavior have a positive effect on employee performance, while task complexity has a negative effect on employee performance. This study supports the theories used previously, namely Attribution Theory and Technology Acceptance Model (TAM).